Rhythmic sonic feedback for speed skating by real-time movement synchronization - Godbout, A.; Boyd, J. E. (International Journal of Computer Science in Sport, 2012)
A unique problem associated with the movements of a speed skating athlete inspired this practical work, looking into the question of using interactive auditory feedback to improve sporting movements and sporting movement acquisition. Presented here is a method for synchronizing the periodic movements of a subject against the movements of a model and sonifying that synchronization data in real-time. The sonic feedback is designed to convey information related to how the movements of a subject match against those of a model. A simple, inexpensive sensor system is created to capture speed skating movements and facilitate the sonification. The effectiveness of the system is demonstrated with two case studies. The first case study involves an experienced skater who had developed a significant anomaly in his technique, who uses this system to become aware of and correct his undesired movements. The second case study involves a new and inexperienced speed skating athlete who accelerates the acquisition of speed skating skills by listening and reacting to the relationship between his movements and those of a skilled speed skating athlete. While speed skating is used to demonstrate this sonic feedback technique, the algorithms can be applied to any repetitive movements.